Preserving cultural identity: The imperative of prioritizing Indonesian character values in English textbooks to safeguard against cultural hegemony in language learning - Sudartini, Siti (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2024)
This article discusses the need to prioritize Indonesian cultural character values in English textbooks as a strategy to maintain cultural identity and counter the hegemony of Western cultural values in language learning in Indonesia. In the context of this research, the phenomenon is based on English textbooks for high school students in grades XI and XII in Indonesia. This research method uses library research. The main instrument of this research is the researcher himself as a